PENGARUH METODE PEMBELAJARAN OUTDOOR LEARNING BERBENTUK JELAJAH LINGKUNGAN TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA - Rizka Awaluddin; Muhammad Wahyu Setiyadi (STKIP Bina Bangsa Meulaboh, 2023)
AbstractThe purpose of this research is to find out how much influence the learning method hasoutdoor learning in the form of environmental exploration on the motivation and learning outcomes of class VII students of SMPN 4 Bolo. Learning methodsoutdoor learning The form of environmental exploration is one method that can motivate students in learning, because in learning activities students are invited out of class to make observations and identify the material being studied. With environmental roaming learning it makes it easier for students to understand the material being taught. This type of research is quasi-experimental research, in experimental research there is a group that is used as an experimental group and there is a group that is used as a control group. Research design usingposttes only control design. The population in the study was all class VII SMPN 4 Bolo consisting of three classes. Samples were randomly selected so that two classes were selected, Class VIIB as the experimental class and class VIIC as control class. The results of the study show (1) there is a significant effect of the learning methodoutdoor learning in the form of environmental exploration on students' learning motivation, (2) there is a significant influence of the influence of learning methodsoutdoor learning form of environmental exploration of student learning outcomes.Keywords: Outdoor learning; Explore the environment, Student learning motivation, Student learning outcomes.6